1999
DOI: 10.1080/019021499270439
|View full text |Cite
|
Sign up to set email alerts
|

GLUCOSE DECREASES STEADY STATE mRNA CONTENT OF HYDROPHOBIC SURFACTANT PROTEINS B AND C IN FETAL RAT LUNG EXPLANTS

Abstract: The streptozotocin-induced diabetic (STZ-DB) rat model is associated with fetal hyperglycemia, but with low to normal plasma insulin concentration. Because surfactant protein (SP) mRNA content in fetal rat lung is decreased in STZ-DB pregnancy, we investigated the effect of increasing concentrations of glucose on SP gene expression in lung organ cultures. SP mRNA content (SP-A, SP-B, SP-C) was assessed by Northern blot analysis in fetal day 20 lung explants (term = 22 days) cultured for 44 hours in medium cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Similarly, the expression of surfactant proteins has been shown to be "obese women have reduced pulmonary function" altered by exposure to increased circulating glucose and insulin concentrations. A study by Rayani et al 85 using pregnant streptozotocin-diabetic rats demonstrated decreased SP-B and SP-C mRNA expression in late gestation lung explants from fetuses that experienced increased plasma glucose but low to normal insulin concentrations. In vivo, induced diabetes in pregnant rats interferes with normal expression patterns of SP-A, SP-B and SP-C mRNA in the developing fetal lung.…”
Section: Fetal Consequences Of Maternal Obesity and Gestational Diabementioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the expression of surfactant proteins has been shown to be "obese women have reduced pulmonary function" altered by exposure to increased circulating glucose and insulin concentrations. A study by Rayani et al 85 using pregnant streptozotocin-diabetic rats demonstrated decreased SP-B and SP-C mRNA expression in late gestation lung explants from fetuses that experienced increased plasma glucose but low to normal insulin concentrations. In vivo, induced diabetes in pregnant rats interferes with normal expression patterns of SP-A, SP-B and SP-C mRNA in the developing fetal lung.…”
Section: Fetal Consequences Of Maternal Obesity and Gestational Diabementioning
confidence: 97%
“…83 Although the molecular mechanisms regulating this outcome were not well understood, it has since been shown that increased plasma glucose and/or insulin concentrations are implicated in the delay of fetal lung maturation, 84 abnormalities in lipid metabolism and decreased surfactant protein mRNA expression. 85 Furthermore, maternal obesity may be linked to persistent pulmonary hypertension in newborns, which can be accompanied by RDS. 86 Maternal diabetes has been associated with a reduction in SP-A in amniotic fluid, suggesting delayed fetal lung maturation.…”
Section: Fetal Consequences Of Maternal Obesity and Gestational Diabementioning
confidence: 99%
“…In fetal rat lung explants, no consistent alteration in SP-A mRNA content was observed at different glucose concentrations (24). Insulin at pharmacological doses inhibited surfactant protein A gene expression in vitro (25,26).…”
Section: Ferná Ndez-real and Associatesmentioning
confidence: 98%
“…Late preterm (34-37 weeks) IDMs commonly have apparent surfactant deficiency respiratory distress syndrome despite their advanced gestational age. Fetal hyperglycemia and hyperinsulinism have been associated with pulmonary immaturity and decreased synthesis and secretion by type II pneumocytes of surfactant phospholipids and their associated proteins [62][63][64][65][66]. Earlier studies indicated that high glucose and insulin concentrations inhibit the production of surfactant by blocking key enzymes in the phosphatidylcholine pathway.…”
Section: Respiratory Disordersmentioning
confidence: 99%